Enhanced accumulation of important bioproducts in Chlorella vulgaris through AGPase gene silencing coupled with polyethylene glycol treatment - Saha, Sumedha; Xaxa, Delrin Shaina; Ghosh, Sudip K.; Maiti, Mrinal K. (Journal of biotechnology, 2025)
Microalgae with rapid growth rate, ability to be cultivated in non-agricultural land, and producing numerous bioactive compounds have attracted attention for biofuel production and extraction of valuable co-products. This work focuses on the development of an industrially viable Chlorella vulgaris strain more suitable for biorefinery by downregulating the ADP-glucose pyrophosphorylase (AGPase) enzyme involved in starch biosynthesis. Transgenic lines of C. vulgaris generated through RNA interference (RNAi) demonstrated diminished starch content with an average of 6.7 % (dry cell weight, DCW) from 10 % (DCW) in the untransformed control, after 5 days of shake flask culture in tris acetate phosphate medium with 16 h:8 h light:dark cycle. Under the same growth condition, the total carbohydrate content decreased by an average of 23.5 %, while the lipid content and carotenoid level improved by an average of 19.3 % and 23 %, respectively, in the RNAi lines compared to the control. RNAi lines showed a higher yield of other important co-products, like protein and exopolysaccharide by an average of 30.6 % and 19.6 %, respectively, compared to the control. Interestingly, when polyethylene glycol (PEG) 6000 (0.5 % w/v) was supplemented in the culture medium of C. vulgaris grown till mid-log phase, RNAi lines along with the untransformed control exhibited enhanced level of valuable metabolites after 7 days of PEG treatment. The average carotenoid content of 25.5 μg/mg was recorded in PEG-treated RNAi lines compared to 15.34 μg/mg in PEG-untreated untransformed control alga. Under the similar growth condition, the average lipid content increased to 22.5 % (DCW) in PEG-treated RNAi lines compared to 16.28 % (DCW) in PEG-untreated untransformed control. Overall, the study encompasses use of genetic engineering tool in combination with the application of biochemical modulator PEG to divert the carbon flux from starch biosynthesis towards improved production of important metabolites in microalga. •AGPase silencing decreased starch content with improved lipid and carotenoid levels.•AGPase downregulation enhanced protein and exopolysaccharide contents.•PEG treatment on RNAi lines positively impacted carotenoid and lipid contents.